Harvard Business Review - Harvard University. Graduate school of business administration (Boston : Harvard University. Graduate school of business administration)
HBR covers a wide range of topics that are relevant to various industries, management functions, and geographic locations. These include leadership, negotiation, strategy, operations, marketing, and finance.
Keywords: Economie; Management